Uterocutaneous Fistula : A Rare Clinical Presentation - Huda, M Durrul; Rahman, M Hafizur; Sultana, Shermin Selina; Shah, M Kabiruzzaman; Hasan, M Mohibul; Ramiz, M Sarwar (TAJ: Journal of Teachers Association, 2018)
A uterocutaneous fistula is a rare clinical presentation that occurs following Cesarean section and other pelvic operations. We report a case of Uterocutaneous fistula which was formed following lower segment caesarean section. USG was helpful in the diagnosis and was treated successfully with fistulectomy and repair of uterine wall. The case highlights the rare complication in caesarean section and diagnosis with USG and experience with its management. TAJ 2012; 25: 87-89